Scales on censorship : real life lessons from School Library Journal - Scales, Pat R. (Rowman and Littlefield, 2015)
This collection of questions from readers and Scales' informative answers are gathered in broad thematic groups to help readers explore the all-too-daily reality of confronting efforts to censor, ban, or otherwise limit open and ready access to materials in our schools and libraries. They were all written in response to active book challenges or questions of intellectual freedom and library ethics. These columns have a ripped from the headlines immediacy even as they reflect the core values and policies of librarianship. Each topic is framed with a brief introductory essay.